THE USE OF BIOLOGICS IN AUTOIMMUNE DISEASE MANAGEMENT: A REVIEW OF RECENT ADVANCES AND CHALLENGES - Abdulmajeed Awadh Almutairi; Majed Saad Alotaibi; Mohammed Awadhallah Aljuaid; Abdulmohsen Maywdh Alzaidi; Ali Hassan Aloufi; Mohmmed Hamdi Althomali; Turki Fahad Alharthy; Yasir Abdul Al Zizi; Saeed Atiah Ahmed Alghamdi; Mohammed Saif Almuntashiri; Nashmeah Abdullah Alshammari; Basim Marzoq Al Hejji (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Biologic therapies have transformed the treatment landscape for autoimmune diseases by targeting specific components of the immune system, offering new avenues for managing conditions traditionally resistant to conventional therapies. These agents, including monoclonal antibodies, fusion proteins, and cytokines, are tailored to modulate immune pathways directly involved in autoimmune pathogenesis, such as tumor necrosis factor (TNF) and various interleukins. The precision of these therapies significantly improves efficacy and patient outcomes by reducing systemic side effects associated with broader immunosuppressive drugs. Despite the benefits, the administration of biologics is associated with several challenges, including the risk of severe infections, the development of anti-drug antibodies, infusion reactions, and potential long-term effects such as increased cancer risk. These adverse reactions are influenced by the complex pharmacodynamics and pharmacokinetics of biologics, which differ markedly from those of small molecule medications. Biologics are typically administered via injection or infusion, necessitating careful monitoring and management strategies to mitigate risks and manage side effects effectively. Pharmacological insights into the mechanisms of action of biologics reveal that they operate by selectively inhibiting key cytokines and immune cells involved in inflammatory processes. However, this can lead to complications like immunosuppression and the paradoxical induction of other autoimmune phenomena. The potential for drug interactions, particularly with other immunomodulatory agents and live vaccines, adds another layer of complexity to treatment regimens, requiring detailed patient assessments and tailored therapeutic approaches. Given these considerations, it is essential to balance the clinical benefits of biologic therapies against their risks. Ongoing research and real-world evidence continue to refine the use of biologics, aiming to enhance safety profiles and develop management strategies that optimize treatment outcomes for patients with autoimmune diseases.